Druggable genome screens identify SPP as an antiviral host target for multiple flaviviruses - Wenjie Qiao; Xuping Xie; Pei-Yong Shi; Yaw Shin Ooi; Jan E. Carette (Proceedings of the National Academy of Sciences, 2025)
Mosquito-borne flaviviruses, such as dengue virus (DENV), Zika virus (ZIKV), West Nile virus, and yellow fever virus, pose significant public health threats globally. Extensive efforts have led to the development of promising highly active compounds against DENV targeting viral non-structural protein 4B (NS4B) protein. However, due to the cocirculation of flaviviruses and to prepare for emerging flaviviruses, there is a need for more broadly acting antivirals. Host-directed therapy where one targets a host factor required for viral replication may be active against multiple viruses that use similar replication strategies. Here, we used a CRISPR-Cas9 library that we designed to target the druggable genome and identified signal peptide peptidase (SPP, encoded by Histocompatibility Minor 13, HM13), as a critical host factor in DENV infection. Genetic knockout or introducing mutations that disrupt the proteolytic activity of SPP markedly reduced the replication of multiple flaviviruses. Although their substrates differ, SPP has structural homology with γ-secretase, which has been pursued as a pharmacological target for Alzheimer’s disease. Notably, SPP-targeting compounds exhibited potent anti-DENV activity at low nanomolar concentrations across multiple primary and disease-relevant cell types, acting specifically through SPP inhibition rather than γ-secretase inhibition. Importantly, SPP inhibitors were active at low nanomolar concentrations against flaviviruses other than DENV including ZIKV while DENV NS4B inhibitors lost activity. This study emphasizes the strong potential of SPP as a pan-flaviviral target and provides a framework for identifying host druggable targets to screen for broad-spectrum antivirals.